Pre-operative/Neoadjuvant Therapy and Vascular Debranching Followed by Resection for Locally Advanced Pancreatic Cancer (PREVADER): Clinical Feasibility Trial - Ronellenfitsch, Ulrich; Michalski, Christoph W.; Michl, Patrick; Krug, Sebastian; Ukkat, Joerg; Kleeff, Joerg (Frontiers in Medicine, 2021)
Introduction Pancreatic cancer continues to have a poor outcome. Many patients are diagnosed with advanced disease, and in a considerable proportion, abutment or invasion of visceral arteries are present. Moreover, some patients have anatomical variations or stenosis of major visceral arteries requiring arterial reconstruction upon pancreatic cancer resection to avoid organ ischemia. Simultaneous arterial reconstruction during resection is associated with relevant morbidity and mortality. This trial evaluates the approach of visceral debranching, i.e. arterial reconstruction, prior to neoadjuvant chemotherapy and tumor resection in patients with locally advanced, unresectable pancreatic cancer. Methods and Analysis The trial includes patients with locally advanced, non-metastatic pancreatic cancer with arterial abutment or invasion (deemed primarily unresectable), variations in vascular anatomy or stenosis of visceral arteries. Participants undergo visceral debranching followed by current standard neoadjuvant chemotherapy (mFOLFIRINOX, Gemcitabine-NabPaclitaxel, or other) and potential subsequent tumor resection. The primary outcome is feasibility, measured as the proportion of patients who start neoadjuvant therapy within six weeks of visceral debranching. The trial has an exact single-stage design. The proportion below which the treatment is considered ineffective is set at 0.7 (H0). The proportion above which the treatment warrants further exploration in a phase III trial is set at 0.9 (H1). With a power (1-beta) of 0.8 and a type-1 mistake (alpha) of 0.05, the required sample size is 28 patients. Feasibility of the approach will be assumed if 24 of the enrolled 28 patients proceed to neoadjuvant chemotherapy within six weeks from visceral debranching. Discussion This trial evaluates a new treatment sequence, i.e. visceral debranching followed by chemotherapy and resection, for pancreatic cancer with invasion or abutment of visceral arteries. The primary objective of the trial is to evaluate feasibility. Trial results will allow for estimating treatment effects and calculating sample size of a randomized controlled trial, in which the approach will be tested if the feasibility endpoint is met. Trial registration ClinicalTrials.gov, NCT04136769. Registered October 21, 2019, https://clinicaltrials.gov/ ct2/show/NCT04136769